MUNASABAH AL-AYAH FI AL-QURAN - MUTIAH MUTIAH; DWI NOVIANI; PEBRIYANTI PEBRIYANTI (Raudhah - Proud To Be Professional, 2022)
ABSTRACT The Qur'an is the word of Allah which is also a miracle, which was revealed to Muhammad SAW. which reached mankind by way of Al-tawâtur (directly from the Prophet to his people), which was then recorded in the Mushaf. Understanding the instructions contained in the Al-Quran needs to be supported by related sciences, for example: asbab an-nuzul, munasabah, makki and madani and so on. The study of the chronological historicity of the revelation of verses is seen from the science of asbab an-nuzul. Not all verses of the Koran have specific asbab nuzul, to complete this, the science of munasabah is offered as an attempt to correlate verses (suras) in the Koran. The source of knowledge from this munasabah is based on ijtihadi, so there are differences about the various types. This paper will discuss the relationship between themes and sub-themes in the educational approach. This study resulted in the use of the term apperception in the education theme, which connects the lessons issued with the lessons to be discussed by linking various related themes. so that the theme of the verse will always be related to the same scientific pattern until the discussion is complete.